HÁZIRGI ZAMAN QARAQALPAQ BALALAR PROZASÍNDA QAHARMAN OBRAZÍ HÁM ONÍŃ OQIWShÍ ShAXSÍNA TÁSIRI - Qosbergenova, Aysanem Muratbaevna (ILIM hám JÁMIYET, 2026)
This article is dedicated to the role of modern Karakalpak children’s prose and the characters depicted in it in shaping the personality of primary school students. Within the framework of the study, the mechanisms of the literary hero’s influence on children’s psychology are analyzed, specifically regarding their emotional-volitional qualitiyes, moral values, and social adaptation. The article also provides recommendations for developing professional and life competenciyes in children through the effective use of fiction in the educational process.